0477 Characteristics of Insomnia Subjects Screened for Transitioning from Zolpidem Tartrate to Lemborexant in a Multicenter Pilot Study. (27th May 2020) - Ahmad, M; Malhotra, M; Amchin, J; Kumar, D; Perdomo, C; Moline, M
Abstract: Introduction: Patients who take insomnia medication may change medications for reasons including lack of efficacy, adverse events, and dependence concerns. A pilot study (NCT04009577, E2006-A001-312) assessed a dosing approach for transitioning patients from zolpidem tartrate (ZOL; immediate or extended-release) to lemborexant, a dual orexin receptor antagonist. Here we describe characteristics of subjects who entered the study Screening Period and their reasons for wanting to change medications. Methods: This multicenter pilot study was conducted in the U.S. and enrolled subjects age ≥18y with insomnia diagnosed per DSM-5 criteria, and who used ZOL (self-reported intermittently [3-4 nights/week] or frequently [≥5 nights/week]) as their only insomnia treatment. Subjects entered a 3-week Screening Period, during which frequency/dose of ZOL taken was recorded; subjects also wore an actigraph continuously. Eligible subjects thereafter entered the Treatment Phase to determine lemborexant dosing (5 or 10mg during a 2-week Titration Period with assignment to 1 of 3 treatment schedules based on ZOL usage frequency during Screening), followed by a 12-week Extension (Maintenance) Phase and a 4-week Follow-up Period. Results: Forty-nine subjects entered the Screening period and completed the Chief Complaint Form through November 2019; mean(SD) age was 57.1(13.8)y, 67.3% were female, 69.4% were white, and 28.6% were black. 31 subjects reported using ZOL frequently and 15 reported using ZOL intermittently (3 missing). The most common sleep complaint was waking up too early (n=33), followed by difficulty staying asleep (n=13), and difficulty falling asleep (n=3). Reasons for wanting to switch from ZOL included: ZOL not working (n=19), concerns about taking ZOL (n=14), wanting to try something new/potentially better (n=6), side effects (n=5), and residual daytime sleepiness (n=4). 43/49 subjects completed screening through this period. Conclusion: This study offers the opportunity to understand patients' current use of insomnia medication and their motivation for wanting to change insomnia medications. Support: Eisai Inc.